2005
DOI: 10.1001/archopht.123.4.458
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA Damage in the Human Trabecular Meshwork

Abstract: To evaluate the intensity of oxidative molecular damage and its clinical correlations: visual field damage, intraocular pressure, age, and disease duration.Methods: DNA was extracted from human trabecular meshwork specimens collected from 17 glaucomaaffected patients using standard filtration surgery. Twentyone specimens from healthy eyes collected for cornea transplants serve as controls. Oxidative DNA damage was evaluated by determining 8-hydroxy-2Ј-deoxyguanosine levels. All patients underwent a Humphrey 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
134
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 322 publications
(140 citation statements)
references
References 28 publications
1
134
0
Order By: Relevance
“…31 Recent evidence demonstrates that there is extensive oxidative DNA damage involving the trabecular cells of patients with POAG, affecting the filtration zone and inner trabecular meshwork layers. 32 Other studies report that incorporating a specific type of myocilin mutant known to be present in vivo in certain types of open angle glaucoma into TMEs in vitro (that is, Pro370Leu) results in ''killing'' of cultured human TMEs. 33 The demise of TMEs is the result of misfolding, aggregation, and build up of this protein in the endoplasmic reticulum of trabecular cells.…”
Section: Discussionmentioning
confidence: 99%
“…31 Recent evidence demonstrates that there is extensive oxidative DNA damage involving the trabecular cells of patients with POAG, affecting the filtration zone and inner trabecular meshwork layers. 32 Other studies report that incorporating a specific type of myocilin mutant known to be present in vivo in certain types of open angle glaucoma into TMEs in vitro (that is, Pro370Leu) results in ''killing'' of cultured human TMEs. 33 The demise of TMEs is the result of misfolding, aggregation, and build up of this protein in the endoplasmic reticulum of trabecular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have identified oxidative damage as an important event in the pathogenesis of ocular diseases such as macular degeneration (Kinnunen et al, 2011), cataract (Varma et al, 2011), and glaucoma (Abu-Amero et al, 2006; Alvarado et al, 1981; Chang, 2006; Chen and Kadlubar, 2003; Ferreira et al, 2004; Gabelt and Kaufman, 2005; Holekamp et al, 2005; Izzotti et al 2003; Izotti et al, 2006; Izzotti et al, 2009; Kong et al, 2009; Liton et al, 2009; Sacca et al, 2005; Sacca et al, 2007; Sacca and Izzotti, 2008; Shui et al, 2006; Siegfried et al, 2010; Tomarev, 2001; Wang et al, 2001; Zhou and Yue, 1999). Two important hemodynamic parameters of oxygen metabolism include oxygen partial pressure ( p O 2 ) and oxygen saturation of hemoglobin (sO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular aging does occur in the trabecular meshwork (TM), the main regulator of aqueous humor outflow [12]. Oxidative damage in TM occur in primary open angle glaucoma [13] and is strictly related with intraocular pressure increase and visual field damage [14]. Indeed, dysfunction of the TM increases the resistance of the outflow pathway and induces an increase in intraocular pressure.…”
Section: Introductionmentioning
confidence: 99%